Effect of structural changes of Pd/WO3 thin films on response direction and rate in hydrogen detection - Han, Seung Ik; Kumar, Mohit; Duy, Le Thai; Yeasmin, Rubaya; Park, Chiwan; Jung, Gwanggyo; Kim, Hyunsup; Khan, Amir Sohail; Dang, Hyunmin; Seo, Hyungtak (Sensors and Actuators B: Chemical, 2024)
Hydrogen (H2) has attracted considerable attention as a renewable energy carrier owing to its recyclability and environmental friendliness. However, due to its explosive nature at concentrations above 4 % in air, the detection of H2 is a critical safety concern. Thereby, this study investigates the impact of the growth forms of the Pd/WO3 thin film layer on the sensor's ability to detect H2, including the response direction and rate of the sensor's resistance change. The chemoresistive sensors were constructed using a nanoporous WO3 film (formed via RF sputtering on a Si/SiO2 wafer) and a palladium layer (deposited via e-beam evaporation). Experimental results display the excellent hydrogen detection performance of the sensors at concentrations ranging from 1- 10 % (in air) by the change of chemoresistance and demonstrate that the strategies used in fabricating the sensors are effective for practical use. By gaining a deeper understanding of the hydrogen sensing mechanisms in Pd/WO3 thin films, this study reveals how to improve the performance of hydrogen sensors and ensure their safe use in various industries.
Keywords: Current direction; Detection of H; Environmental friendliness; Growth form; Hydrogen detection; Hydrogen sensor; Recyclability; Renewable energy carrier; Safety concerns; Thin-films; Current direction; Hydrogen sensors; Palladium; Thin film; Tungsten oxide